PERENCANAN PEMBANGUNAN DESA KIE-ICI DI KECAMATAN IBU KABUPATEN HALMAHERA BARATPERENCANAN PEMBANGUNAN DESA KIE-ICI DI KECAMATAN IBU KABUPATEN HALMAHERA BARAT - OLLO, DEWANTI SRI (JURNAL ADMINISTRASI PUBLIK, 2018)
One of the outstanding things of the Indonesian nation so far is to implement national development in all areas in a planned, gradual and continuous manner with particular emphases at each stage in accordance with the demands and development of the era. National development is a reflection of the will to continuously improve prosperity and prosperity the people of Indonesia in a fair and equitable way, as well as developing the life of society and the implementation of a developed country and democracy based on Pancasila. From the observations made in the village of Kie-Ici District of Halmahera Barat District, it seems that the village development planning has not been maximally effective. This is due to the lack of leadership of village heads in village development planning and the lack of proper functioning of the Community Empowerment Institution (LPM) in carrying out its duties and functions in village development planning. In addition, community social organizations or groups within the community phave not been involved in village development planning meetings. (RPMJD) for a period of 5 (five) years, and RKP-Desa for a period of 1 (one) year, as stipulated in article 78-82 of Law No. 6 Year 2014 on Village, and Minister of Home Affairs Regulation no. 114 of 2014 on Village Development Guidelines. To find out how the rural development planning function was implemented in KeiIci Village, interviews with informants were conducted. The number of informants who were successfully interviewed were 5 (five) heads: Kei-Ici Village Head, Section Head of Kei-Ici Village Development, Head of BPD Desa Kei-Ici, Village LPM Chairman Kei Ici, and one citizen. Conclusion Village planning planning in Kei-Ici village is done through Forum of Village Development Planning (Musrembang). And Implementation Musrembang held in accordance with the provisions of legislation on village development. Before Musrembang begins with the village level (Mudus) Musyawarah for problem selection and village potency. The Village Development Plan (RPJMD) and RKPD (Village Development Plan) (RKPD) are generally in accordance with the existing problems in the village, village potential, and the needs of the village community so that they can be implemented / realized properly. Keywords: Development Planning in Kie-ici Village